Towards a consensus on a hearing preservation classification system. (December 2013) - Skarzynski, Henryk; van de Heyning, P.; Agrawal, S.; Arauz, S. L.; Atlas, M.; Baumgartner, W.; Caversaccio, M.; de Bodt, M.; Gavilan, J.; Godey, B.; Green, K.; Gstoettner, W.; et al.
Abstract: Conclusion: The comprehensive Hearing Preservation classification system presented in this paper is suitable for use for all cochlear implant users with measurable pre-operative residual hearing. If adopted as a universal reporting standard, as it was designed to be, it should prove highly beneficial by enabling future studies to quickly and easily compare the results of previous studies and meta-analyze their data. Objectives: To develop a comprehensive Hearing Preservation classification system suitable for use for all cochlear implant users with measurable pre-operative residual hearing. Methods: The HEARRING group discussed and reviewed a number of different propositions of a HP classification systems and reviewed critical appraisals to develop a qualitative system in accordance with the prerequisites. Results: The Hearing Preservation Classification System proposed herein fulfills the following necessary criteria: 1) classification is independent from users' initial hearing, 2) it is appropriate for all cochlear implant users with measurable pre-operative residual hearing, 3) it covers the whole range of pure tone average from 0 to 120 dB; 4) it is easy to use and easy to understand.